Enhanced StefinA and Sprr2 expression during papilloma formation in HPV8 transgenic mice - Miller-Lazić, Daliborka; Alborzi, Farnoosh; Marcuzzi, Gian Paolo; Angel, Peter; Heß, Jochen; Pfister, Herbert; Akgül, Baki (Journal of dermatological science, 2011)
Background - The human papillomavirus type 8 (HPV8) is associated with the development of non-melanoma skin cancer. Transgenic mice expressing the complete early gene region of HPV8 (E6/E7/E1/E2/E4=CER) or E6 separately under the control of the keratin14 promoter spontaneously developed papillomas characterized by varying degrees of epidermal dysplasia. Papilloma growth could be synchronized by a single UVA/B irradiation of the skin, which led to the development of papillomas within three weeks. - Objective - The objective of this study was to identify alterations in cellular gene expression correlated with HPV8 oncogene expression in transgenic mice. - Methods - We applied global gene expression profiling by microarray analysis and confirmed deregulation of cellular genes by qRT-PCR and immunohistochemical analysis. - Results - By comparison of non-lesional HPV8-CER skin with skin of the parental mouse strain FVB/n, two cellular genes, namely StefinA and Sprr2, coding for precursor proteins of the cornified envelope, were predicted to be strongly upregulated in transgenic skin, which could be confirmed in subsequent qRT-PCR experiments. StefinA and Sprr2 mRNA expression was enhanced until day 7 after UV treatment with higher levels in HPV8 positive skin. While the expression of both genes returned to a normal level in the course of epidermis regeneration in wt mice, the expression persisted elevated in hyperplastic transgenic skin. Staining of an UV induced papilloma of FVB/n wt mouse revealed also strong expression of StefinA and Sprr2 indicating that upregulation in later stages of papilloma formation is independent of HPV8. - Conclusion - In non-lesional HPV8-CER transgenic skin StefinA and Sprr2 were found to be indirect/direct transcriptional targets of HPV8.
Gesehen am 13.07.2022